PROGRAM TEXT, PROGRAMMING STYLE, PROGRAMMER LABOR: Some Further Comments on Comments. - Lennon, Brian (Cultural Politics (Duke University Press), 2018)
Computer programming can be understood as both a kind of writing and a special class of human labor activity facilitating the automation of other human labor activities, not excluding itself. From the very beginning of the history of computer programming, it was recognized that the technical logic of programming is a logic of automation, indeed, a logic of self-automation or even recursive automation. This article suggests that a syntactic feature common to all programming languages used today serves as a register of this logic of automation, leaving traces in code that are legible if one knows where to look. That feature is the comment: natural-language text within a computer program that is written exclusively for human readers of the program and is separated from executable code, though it stands alongside it. At their most interesting, in patterns of use to which a managerial discourse of software craftspersonship is actively hostile, yet to which so-called literate programming practice is indifferent, program comments are traces of a mode of technical labor whose privilege and precarity both rest on its obscurity, an obscurity in no way resistant to reading.